Pengaruh Paham Feminisme Terhadap Penurunan Populasi Penduduk di Jepang『少子化』 - Sri Dewi Adriani (Humaniora, 2014)
Modern Japanese society is currently experiencing a lot of social problems. One of them is a decrease in birth rate. The reason is the increase of feminism understanding on the modern Japanese women. Article discusses the impact of feminism thought development on the decline of Japanese population. The purpose of the study is to determine the influence of feminism thought in modern Japanese women’s point of view on childbirth. Research used qualitative approach with descriptive analytical method. From the analysis conducted, it can be concluded that problem in the decadence of birth rate is influenced by feminism thought among the modern Japanese women.